IMPROVING THE METHODOLOGY OF TEACHING MOLECULAR PHYSICS IN HIGHER EDUCATION BASED ON ELECTRONIC LEARNING RESOURCES - M.M. Quchqorova, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This study examines the methodological foundations for improving the teaching of molecular physics in higher education through the integration of electronic learning resources  (ELRs).  The  research  highlights  the  role  of  digital  technologies,  virtual laboratories,  and  interactive  simulations  in  enhancing  students’  conceptual understanding of microscopic physical processes.  The  paper  proposes  a  model  for  integrating  ELRs  into  the  curriculum  and evaluates its effectiveness through pedagogical analysis. The results demonstrate that the use of ELRs significantly improves students’ engagement, independent learning skills, and academic performance.